Gestión de Proyectos con Tecnologías de Información y Comunicación en la educación básica y media de Colombia (2022)
Currently, the Colombian and the world education sector is undergoing a transformation due to the evolution of Information and Communication Technologies (ICT), therefore, ICT policies have been established for education at all levels and resources have been allocated for their development and literacy as a 21st century competence. However, the strategies implemented within formal educational institutions have not achieved the scope set in ICT goals. This article has been developed on the need to visualize the educational institutions of basic and secondary education as organizations to achieve an efficient management of ICT projects. Moreover, some ICT integration experiences are compiled to set out their implementation as an advance in the integration of administrative, organizational and pedagogical aspects that are consistent with Project Management standards in the achievement of results and goals aligned to the educational institutional context.